Protection of a Pregnant Woman and a Child Conceived in Canon Lawand Norms of other Religions. - WROCEŃSKI , JÓZEF (Prawo Kanoniczne, 2019)
Protection of a Pregnant Woman and a Child Conceived in Canon Lawand Norms of other Religions. In his study, the author discusses the important issue of protecting a pregnant woman and conceived life in almost all well known world religions. This problem, he notes, leads to a number of fundamental religious, ethical, legal, and philosophical disputes, because it concerns an important element in the construction of the normative order of each society. The analysis of the issue begins with a brief discussion of the concept of religion and emphasizes that a woman occupies an important place in each religion, and the period of pregnancy and childbirth is considered a special time, not only for her, but for the whole family and the community in which she lives. Then he analyzes the law of the Catholic Church in the discussed matter, emphasizing that the legislation of the Church provides for the abortion, for whatever reasons, the heaviest punishment, namely the penalty of excommunication latae sententiae. Next, after analyzing the regulations of other religions, he notices that not only the Catholic Church radically rejects the admissibility of termination of pregnancy, but no religion explicitly supports abortion, recognizing this act as a crime and providing for appropriate sanctions. However, the rules of each religion contain exceptions where pregnancy may be terminated in special circumstances. Usually these exceptions are justified by the mother's state of health. In the summary, the author formulates the conclusion that only granting an unborn child legal subjectivity under positive law would be tantamount to granting him rights and duties in the legal system of each religion. For now, it seems that the more appropriate term would be to use the term 'human being' in relation to the unborn child.